2008
DOI: 10.1007/s00059-008-3098-0
|View full text |Cite
|
Sign up to set email alerts
|

Akutintervention (Primär-PCI) im Rahmen des Essener Herzinfarktverbundes

Abstract: In a German city (Essen, 490,000 people), a new network system for patients with ST elevation myocardial infarction (STEMI) was established in 2004. This included a so-called integrated care model (IV model) by participation of insurance companies. In a cooperative structure between invasive and noninvasive hospitals, general practitioners and cardiologists as well as emergency systems it could be realized, that every patient with STEMI will be treated by primary percutaneous coronary intervention (PCI) as soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
0
0
1
Order By: Relevance
“…Accordingly, better coordination and direct patient transfer to the catheter laboratory could lead to a reduction in DTB times in the PCI centres. Finally, the documented median total ischemia time of 181 min achieved in our network is comparable to European data derived from Germany (239 min) [ 15 ], Hungary (223 min) [ 16 ] and Sweden (175 min) [ 14 ]. In the APPOSITION-III trial, total ischemia times of 165, 270 and 360 min were reported for the Netherlands, Germany and France, respectively [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, better coordination and direct patient transfer to the catheter laboratory could lead to a reduction in DTB times in the PCI centres. Finally, the documented median total ischemia time of 181 min achieved in our network is comparable to European data derived from Germany (239 min) [ 15 ], Hungary (223 min) [ 16 ] and Sweden (175 min) [ 14 ]. In the APPOSITION-III trial, total ischemia times of 165, 270 and 360 min were reported for the Netherlands, Germany and France, respectively [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…Aus dem Herzinfarktverbund in Essen berichten R. Jacksch et al über die Ergebnisse der Akutintervention im Rahmen des ersten in Deutschland realisierten Herzinfarktverbundes im Rahmen eines integrierten Versorgungsmodells [16].…”
unclassified